Anaplastic lymphoma kinase positive variant of anaplastic large cell lymphoma: A rare entity - Venkata Satya Ramesh Thummala; Sreenidhi Banda; Vinay Kumar Reddy Kundoor; Kotya Naik Maloth (Wolters Kluwer Medknow Publications, 2014)
Anaplastic large cell lymphoma (ALCL) is a distinct clinicopathological entity of non-Hodgkin's lymphoma, which has been included as a T-cell neoplasm in the World Health Organization classification, with peculiar features such as painless lymphadenopathy, swelling of extranodal and endoreticular organs, intraoral swellings, and characteristic hallmark cells (eccentric, kidney-shaped, or horseshoe-shaped nuclei) and cluster of differentiation 30 (CD30) positivity. Thorough clinical, biochemical, immunohistochemical, histopathological, and radiological evaluation aids in accurate diagnosis and management of the disease. Here, we report a case of anaplastic lymphoma kinase positive variant of ALCL in a 13-year-old boy.